To rearrange the formula y = mx + b using x as the quantity of interest, the first step would be to isolate x on one side of the equation.
Starting with the given formula:
y = mx + b
We want to express x in terms of the other variables.
First, subtract b from both sides of the equation:
y - b = mx
Now, we have mx on one side of the equation.
Next, divide both sides of the equation by m:
(y - b)/m = x
Now, we have x isolated on one side of the equation, and the formula is rearranged to express x as the quantity of interest.
Using the Property of Equality, what first step would you take to rearrange the formula y=mx+b using x as the quantity of interest?
1 answer